2017
DOI: 10.1007/s13205-017-0766-x
|View full text |Cite
|
Sign up to set email alerts
|

Antidepressant and anxiolytic effects of Garcinia indica fruit rind via monoaminergic pathway

Abstract: Depression and anxiety are the most crippling neuropsychiatric disorders of this modern era. These mostly occur as anxiety followed by depression or in mixed state. Therefore, there is an urgent need of a safe and effective treatment, which proves its worth in this ailment. What else than a conventional food would be a better choice for a convenient therapy. Therefore, Garcinia indica, commonly known as Kokam, fruit rind has been used in the present study to investigate its antidepressant and anti-anxiety pote… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
19
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(22 citation statements)
references
References 66 publications
1
19
2
Order By: Relevance
“…No difference in the total distance traveled was seen among all groups, suggesting that locomotor activity has been affected neither by CIS nor HECO. These results are consistent with behavioral data from other studies showing no effect of chronic stress or anxiolytic treatment on locomotor activity (Dhamija, Parle, & Kumar, 2017; Jiang et al, 2018) while some studies (Mehta et al, 2017; Tayyab et al, 2019; Wang, An, & Zhang, 2008) reported decreased locomotor activity in stressed animals comparing to treated one. The reason for this discrepancy may relate to the use of different strains of animals, the open field arena dimensions, chronic stress procedures, and drugs.…”
Section: Discussionsupporting
confidence: 90%
“…No difference in the total distance traveled was seen among all groups, suggesting that locomotor activity has been affected neither by CIS nor HECO. These results are consistent with behavioral data from other studies showing no effect of chronic stress or anxiolytic treatment on locomotor activity (Dhamija, Parle, & Kumar, 2017; Jiang et al, 2018) while some studies (Mehta et al, 2017; Tayyab et al, 2019; Wang, An, & Zhang, 2008) reported decreased locomotor activity in stressed animals comparing to treated one. The reason for this discrepancy may relate to the use of different strains of animals, the open field arena dimensions, chronic stress procedures, and drugs.…”
Section: Discussionsupporting
confidence: 90%
“…Garcinol, has been well distinguished to possess potential anti-cancer properties attributed to the ability to inhibit HATs, NF-κB and STAT [33]. Furthermore, this pleotropic compound's activity spectra includes antibiotic [117], anti-inflammatory [118], antioxidant, antidepressant, and anxiolytic [119] properties via modulation of key regulatory cell signaling cascades.…”
Section: Synergistic Effects Of Garcinolmentioning
confidence: 99%
“…Traditional use of G. cambogia fruit pericarp extracts in multiple traditional medicinal system to treat bacterial diseases and cancer was validated by Hart and Cock (2016). The juice and ethanolic extract of G. mangostana leaves have possible antifungal and antibacterial activity (Diniatik et al, 2019) whereas the fruit rind of G. indica has significant antidepressant and anxiolytic effect (Dhamija et al, 2017). The main component of fruit rind is garcinol, isogarcinol and camboginol.…”
Section: Introductionmentioning
confidence: 99%